The Efficiency of Solar Power Generation System Application on Agricultural Automatic Drip Irrigation in Indonesia - Muhammad Joni Iskandar; Huswatun Ida Lailatun Hasanah; Rini Endang Prasetyowati; Muhammad Anwar (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Irrigation is one of the important components of farming producers in cultivation. Lack of irrigation water causes crop failure risk, while excess water also causes agricultural crop failure. It is necessary to regulate irrigation water to achieve technical and economic farming efficiency. This study aims to determine the efficiency of solar power generation in agricultural automatic drip irrigation. This study uses experimental research with the design of materials and research tools. Efficiency estimation uses a simple ratio by looking at the cost components of each treatment so that the value that appears becomes the final efficiency value. This study showed that automatic drip irrigation for solar power generation was more economically efficient than ordinary electricity. The use of automatic drip irrigation can save costs of Rp. 4,346,200. In addition, unlimited renewable energy support is a major advantage besides being environmentally friendly and an agricultural climate change adaptation strategy. The system’s performance on the automatic pump is running well, as seen from P1, P2, P3, P4, and P5; the pump turns on at a percentage of water ranging from 10-90% and turns off after reaching 100% water or water-saturated soil conditions. The main obstacle faced during the research was the climate problem because this research model used the solar system. This means that as long as sunlight shows its existence, the energy obtained is also perfect, but vice versa. In addition, it is still difficult for traditional farmers to carry out the operational control system, so further research is needed.